2010
DOI: 10.1021/om100201x
|View full text |Cite
|
Sign up to set email alerts
|

1,4-Dihydro-1,4-diarsinine-Bridged Dinuclear trans-Dihaloplatinum(II) Complexes: Synthesis and Controlled Pt−Pt Interaction by Halogen Substitution Induced Conformational Change

Abstract: Mono- and dinuclear trans-dichloroplatinum(II) complexes, i.e., trans-PtCl2(cis-DHDAtBu)2 and trans,trans-Pt2Cl4(cis-DHDAtBu)2, respectively, using cis-1,4-dihydro-1,4-dimethyl-2,3,5,6-tetrakis(tert-butoxycarbonyl)-1,4-diarsinine (cis-DHDAtBu), which was prepared by the radical reaction of pentamethylcyclopentaarsine (cyclo-(MeAs)5) and di-tert-butyl acetylenedicarboxylate, were obtained individually as only products by stoichiometric addition of cis-bis(benzonitrile)dichloroplatinum to cis-DHDAtBu. Replacemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…During the course of our studies on the synthesis of a number of different complexation structures of 1,4-dihydro-1,4-diarsinines as cyclic ditopic organoarsenic ligands to transition metals, we have found that flexibility of the bond angles around the arsenic center is an inherent property of the organoarsenic compounds. 10 The flexibility of the arsenic ligands might be a main reason for the nonluminescent properties of most of these organoarsenic complexes at room temperature, in contrast to their phosphorus analogues. We found, as described herein, that a nonporous crystalline solid of an organoarsenic platinum(II) complex shows on−off solid-state luminescence switching through reversible and guest-selective uptake and escape.…”
mentioning
confidence: 99%
“…During the course of our studies on the synthesis of a number of different complexation structures of 1,4-dihydro-1,4-diarsinines as cyclic ditopic organoarsenic ligands to transition metals, we have found that flexibility of the bond angles around the arsenic center is an inherent property of the organoarsenic compounds. 10 The flexibility of the arsenic ligands might be a main reason for the nonluminescent properties of most of these organoarsenic complexes at room temperature, in contrast to their phosphorus analogues. We found, as described herein, that a nonporous crystalline solid of an organoarsenic platinum(II) complex shows on−off solid-state luminescence switching through reversible and guest-selective uptake and escape.…”
mentioning
confidence: 99%
“…The reasons for the quantitative formations of these complexes are the structural advantage of the ligands and properties of the arsenic donor. The interior angles at around the arsenic and the As C C bond angles were significantly varied in a series of the platinum(II) complexes [19]. These observations suggest that the flexibility of the bond angles at around the arsenic center is inherent property in the present cyclic ditopic organoarsenic ligands and the flexibility might be the main reason for stabilization of the strained complexes and enable synthesis of the unique structured complexes.…”
Section: Introductionmentioning
confidence: 82%
“…The 1 H NMR spectrum of PtAu 2 Cl 4 (cisDHDAtBu) 2 in CDCl 3 at room temperature shows the sharp two peaks at δ 1.97 ppm and 1.94 ppm corresponding to the protons of the methyl groups on the arsenic atoms; each peak is attributed to the coordinated methylarsine group to Pt and Au, respectively. In the 1 H NMR spectrum of transPtCl 2 (cis-DHDAtBu) 2 in CDCl 3 at room temperature, the sharp two peaks are observed at δ 1.99 ppm and 1.37 ppm corresponding to the protons of the methyl groups on the arsenic atoms; each peak is attributed to the coordinated methylarsine group and the uncoordinated one, respectively [19]. The later peak is shifted to a downfield by the complexation with Au.…”
Section: Hetero-nuclear Gold(i)-platinum(ii) Complexesmentioning
confidence: 98%
See 2 more Smart Citations